Characterization of leaf-rollers attacking forest and fruit trees in Azerbaijan (Lepidoptera: Tortricidae). - Maharramova, Sheyda (Contributions to Entomology = Beiträge zur Entomologie, 2011)
Characterization of the leaf-roller moths (Tortricidae) attacking forest and fruit trees in the North (Sheki-Zagatala), East (Baku-Absheron), and South (Lenkoran-Astara) regions of Azerbaijan was conducted over the decade 1994-2004. Sixteen species of leaf-rollers representing 14 genera were found to be widespread throughout the regions - 9 species of Tortricinae and 7 species of Olethreutinae. Four species, Ptycholoma lecheana (L.), Cacoecimorpha pronubana Hübner, Eudemis profundana (Denis & Schiffermüller), and Epinotia demarniana (Fisch.), are newly recorded for Azerbaijan. Tortrix viridana L. represented 46.0% of the total number of specimens, Archips rosanus L. 28.0%, and Archips xylosteanus L. 20.2%. Keywords Food plants, pest species, leaf-roller, caterpillar, pupa, imago.